The Motivation of Elementary School Teachers for the Implementation of the Distance Learning Concept - Stojanovska, Vera; Ikonomoska, Angela (Zbornik odseka za Pedagogiju, 2024)
At the center of this research is the motivation of the teaching staff for the overall organization and implementation of the distance learning concept in elementary schools. This study's sample consists of 252 teachers, 118 of whom are class teachers and 134 of whom are subject teachers from 11 elementary schools. A questionnaire was used to obtain information about teachers' motivation for implementing the distance learning concept. The data obtained from the research was processed using a descriptive and quantitative method. The chi-square test was used to assess the existence or non-existence of a difference in teachers' answers. Based on the obtained results, it was concluded that a large percentage of the teachers were motivated to realize the concept of distance learning, but also that there is a difference in motivation between teachers with different work experience but not between class and subject teachers.